2021
DOI: 10.1371/journal.pone.0256632
|View full text |Cite
|
Sign up to set email alerts
|

People’s naïve belief about curiosity and interest: A qualitative study

Abstract: The purpose of this study was to critically examine how people perceive the definitions, differences and similarities of interest and curiosity, and address the subjective boundaries between interest and curiosity. We used a qualitative research approach given the research questions and the goal to develop an in-depth understanding of people’s meaning of interest and curiosity. We used data from a sample of 126 U.S. adults (48.5% male) recruited through Amazon’s Mechanical Turk (Mage = 40.7, SDage = 11.7). Sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 73 publications
(101 reference statements)
0
9
0
Order By: Relevance
“…First, our proposed framework sheds new light on how we understand the developmental trajectories of curiosity and interest. There are common beliefs about the developmental changes of curiosity and interest, such as “younger children are more curious” and “older adults lose curiosity and interest as they age” (see Aslan et al, 2021). Some research findings support this view: Previous studies using survey questions have found that curiosity and interest in school-aged children decreases over time (Gottfried et al, 2001; Spinath & Steinmayr, 2008; Wigfield et al, 2006), and that older adults exhibit decreased curiosity in comparison to younger adults (Robinson et al, 2017; Ziegler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, our proposed framework sheds new light on how we understand the developmental trajectories of curiosity and interest. There are common beliefs about the developmental changes of curiosity and interest, such as “younger children are more curious” and “older adults lose curiosity and interest as they age” (see Aslan et al, 2021). Some research findings support this view: Previous studies using survey questions have found that curiosity and interest in school-aged children decreases over time (Gottfried et al, 2001; Spinath & Steinmayr, 2008; Wigfield et al, 2006), and that older adults exhibit decreased curiosity in comparison to younger adults (Robinson et al, 2017; Ziegler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…and interest as they age" (see Aslan et al, 2021). Some research findings support this view: Previous studies using survey questions have found that curiosity and interest in school-aged children decreases over time (Gottfried et al, 2001;Spinath & Steinmayr, 2008;Wigfield et al, 2006), and that older adults exhibit decreased curiosity in comparison to younger adults (Robinson et al, 2017;Ziegler et al, 2015).…”
Section: Future Directionsmentioning
confidence: 93%
“…In addition, this construct is always intellectualized as being content-specific (Kang et al, 2021;Wild, 2022), which proposes that a student may be interested in a particular subject but not in the other way around, or vice versa. Also, interest has been characterized as a complex construct that encompasses two domains: the affective (e.g., positive feeling) and cognitive (e.g., perceived importance) domains (Aslan et al, 2021;Svenningsson et al, 2022). Concerning this particular concept, educational researchers have concentrated their attention on the study of situational interest, establishing it as superior to individual interest in terms of both its level and the amount of motivational potential it possesses.…”
Section: Individual Interest In Philippine Folk Dance and School Enga...mentioning
confidence: 99%
“…Thus, there is a wide range in how seriously different students take Physical Education or other subjects. Affective (such as a good feeling) and cognitive (such as perceived importance) categories have also been identified in the conceptualization of the idea [39,40]. Regrettably, pedagogical experts have argued that situational interest, especially in a daily teaching-learning scenario, has significantly greater positive consequences than its counterpart.…”
Section: The Nexus Between Individual Interest and School Engagementmentioning
confidence: 99%